Perinatal outcome in terminal oligohydramnios - Rajeshree Tukaram Patil (Asian Journal of Medical Sciences, 2017)
Background of the Study: Amniotic fluid or liquor, the fluid around the developing fetus serves various functions. A balance of formation and reabsorption of this fluid has to be maintained. The amniotic fluid volume (AFV) undergoes changes during pregnancy. Oligohydramnios is a condition in which the AFV decreases and is associated with conditions like renal agenesis, placental dysfunction, congenital anomalies, anemia, PIH, hypoxia. Its effects depend on the duration of pregnancy. But when AFV decreases terminally, the chances of having a normal baby are more.